Enhanced fracture toughness of Al and Bi co-doped Mg2Si by metal nanoparticle decoration. Issue 15 (15th October 2017) - Kim, Gwansik; Lee, Hwijong; Kim, Jeongmin; Roh, Jong Wook; Lyo, Inwoong; Kim, Byung-Wook; Lee, Kyu Hyoung; Lee, Wooyoung
Abstract: We herein report the effects of metal nanoinclusions (Cu, Al, and Sn) embedded at grain boundaries on the thermoelectric transport and mechanical properties of Mg2 Si-based compounds. Hybrid powders of microscale Al and Bi co-doped Mg2 Si (Mg1.96 Al0.04 Si0.97 Bi0.03 ) and nanoscale metal particles were synthesized by a nanometal decoration technique and their nanocomposites were fabricated by a spark plasma sintering process. In compacted polycrystalline bulks, homogeneous dispersion of metal nanoparticles (~150 nm) was readily achieved at grain boundaries. The thermoelectric performance of the nanocomposites deteriorated mainly because of the reduced mobility owing to intensified electron scattering at the phase boundaries between the Mg2 Si matrix and metal nanoinclusions, while the fracture toughness (~1.10 MPa m 1/2, 35% improvement) was significantly enhanced on introducing Al nanoparticles.